Passion For Saving Life In Michael J. Basset's Solomon Kane Movie (2009) : An Existentialist Approach - Istanto D.C, Dery (2012)
This study is aimed to show passion for saving life in Solomon movie by using existentialist perspective. It is done by establishing two objectives: the first is analyzing the movie based on its structural elements and the second is analyzing the movie based on the Existentialist Perspective. This research is qualitative research. Type of data of the study is text and image taken from two data sources: primary and secondary. The primary data source is the Solomon Kane movie directed by Michael J. Basset released in 2009. While the secondary data sources are other materials taken from books, journals, and internet related to the study. Both data are collected through library research and analyzed by descriptive analysis. The study comes to the following conclusions. First, based on the structural analysis of each elements, it shows that the character and characterization, casting, plot, setting, point of view, theme, mise en scene, cinematography, sound, and editing are related to each other and form a unity. Second, based on the Existential analysis, passion for saving life leads to meaningful action in human's life.